Exploring The Adoption Of Building Information Modelling (BIM) In The Malaysian Construction Industry: A Qualitative Approach - Zahrizan, Zakaria; Nasly, Mohamed Ali; Ahmad Tarmizi, Haron; Amanda, Marshall-Ponting; Zuhairi, Abd. Hamid (IJRET, 2013)
The construction industry believes that Building In formation Modelling (BIM) is a platform that has th e potential to promote collaborative activities in the construction indust ry. Thus, clients are gradually enforcing the use o f BIM in their projects, resulting in many construction companies investing in BIM techno logy in order to fulfill clients' needs. Therefore, the goal of this study is to explore the process and the level of BIM implementa tion in the Malaysian construction industry. This s tudy was conducted as an exploratory study through literature review and int erviewing the organisations that have had BIM exper ience. The result reveals that Malaysian construction industry players are having difficulties to implement BIM because they do not k now where, when and how to start as there is no national BIM standard and guid eline for them to follow. Lack of government involv ement worsens the current situation besides having the resistance to change f rom people. To reduce the resistance from people, m ost of the companies came out with their own strategy such as developing new BIM unit, developing training and education program, ch anging management style and developing new roles and responsibilities. Thes e activities could facilitate people and the organi sations in adopting BIM because BIM is not only a technology but it is also involve d in changing the current practices and processes i ncluding changing managerial function and hierarchy, including roles and respons ibilities. Small to medium scale pilot projects can be described as the best practice to adopt BIM in reducing the risk when migrating fr om the traditional approach to a new approach. This study also identified that BIM Level in the Malaysian construction industry is between Level 0 and 1.